Library education and rural information provision in Ghana - Alemna, A.A. (Information development, 1991)
Examines the role that the Department of Library and Archival Studies of the University of Ghana might play in assisting the establishment of rural libraries in Ghana. Reviews the present state of rural information provision in Ghana. The present curriculum of the Department of Library and Archival Studies is not designed to produce librarians able to meet the needs of rural people. Makes suggestions for improvements in the curriculum while maintaining a balance between national needs and international standards.